ANALISIS PERUBAHAN GARIS PANTAI DAN TUTUPAN LAHAN PASCA TSUNAMI PANTAI LHOKNGA, KECAMATAN LHOKNGA, KABUPATEN ACEH BESAR - Tia Novita Siregar; Anita Zaitunah; Samsuri Samsuri (Program studi Kehutanan USU, 2016)
This research describes coastline and land cover changes of Lhoknga beach after tsunami. This research used images satellite of Landsat 5 and Landsat 8. Image interpretation used supervised classification approach with the method of Maximum likelihood classifier. Image interpretation used visual analysis based on monogram North Sumatra. The research showed that coastline changes are caused by abrasion and accretion. Abrasion reduced the area of the beach 45,81 hectares in the period 2000 to 2013. Accretion increased the area of the beach 36,99 ha in the period 2000 to 2013. The largest land cover change between 2000 and 2005 were open land and bush. The open land increased 716.95 ha and bush reduced 1.658,98 ha. The largest land cover changes in the period 2005 to 2013 were bush and forest. The bush increased 1.078,22 ha and forest reduced 823,01 ha. Key words: coastline change, land coverage, Aceh tsunami, Lhoknga Beach.